2012
DOI: 10.1007/s13197-012-0636-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of Simarouba glauca seed fat

Abstract: Simarouba glauca DC is a tree of the family Simaroubaceae, which grows well up to 1,000 m above sea level in all types of well-drained soils (pH 5.5 to 8.0) and in places with 250 to 2,500 mm annual rainfall. The seed oil has been extracted both by mechanical expelling and solvent extraction. The fatty acid composition and iodine value of the oil indicate that it possesses saturated (40.8-42.6%), monounsaturated (52.9-55.0%), and polyunsaturated (2.5-3.4%) fatty acid in ratios close to that of palm oil. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…On contrary, a very negligible amount of unsaponifiable material was co-extracted along with the fatty oil. Thus, the hexane extracted oil also needs refining to ensure its safe use in food products (Rout et al 2014). Over all, the present analysis of P. tetragonolobus oil contained 75.5 % USFA and 21.9 % SFA, whereas soybean oil contained around 86 % of USFA and 14 % SFA (Garcia and Palmer 1979).…”
Section: Composition Of Fatty Oilmentioning
confidence: 74%
See 1 more Smart Citation
“…On contrary, a very negligible amount of unsaponifiable material was co-extracted along with the fatty oil. Thus, the hexane extracted oil also needs refining to ensure its safe use in food products (Rout et al 2014). Over all, the present analysis of P. tetragonolobus oil contained 75.5 % USFA and 21.9 % SFA, whereas soybean oil contained around 86 % of USFA and 14 % SFA (Garcia and Palmer 1979).…”
Section: Composition Of Fatty Oilmentioning
confidence: 74%
“…The oils were converted to corresponding fatty acid methyl ester (FAME) as per our previous reported procedure (Sahoo et al 2003;Rout et al 2014).…”
Section: Gc-fid and Gc/ms Analysis Of Fatty Acid Methyl Esters And Unmentioning
confidence: 99%
“…In this study, toxicity of ethanol leaf extract of S. glauca was tested. Several studies on acute toxicity of a number of related and unrelated plants have been reported [37,54,55]. [38] also reported that stem bark ethanol extract of S. versicolor (which belongs to the same family, Simaroubaceae) when administered to Wistar rats for 30 days; did not result to any observable signs of toxicity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The Sub-Chronic toxicity study was conducted as prescribed in [36] test guidelines, N0. 425; described by [37,38]. A suitable dose range was adopted for the sub-chronic toxicity study.…”
Section: Sub-chronic Toxicity Studies (In-vivo)mentioning
confidence: 99%
See 1 more Smart Citation